2007
DOI: 10.1111/j.1365-3156.2006.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a mass distribution programme for fine‐mesh impregnated bednets against visceral leishmaniasis in eastern Sudan

Abstract: SummaryDuring an epidemic of visceral leishmaniasis (VL) in eastern Sudan, Médecins Sans Frontières distributed 357 000 insecticide-treated bednets (ITN) to 155 affected villages between May 1999 and March 2001.To estimate the protective effect of the ITN, we evaluated coverage and use of ITN, and analysed VL incidence by village from March 1996 to June 2002. We provided ITN to 94% of the individuals >5 years old. Two years later, 44% (95% CI 39-48%) of nets were reasonably intact. Because ITN were mainly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 20 publications
(39 reference statements)
3
67
1
1
Order By: Relevance
“…Such information is important as promoting population expansion of genetically determined resistant dogs would significantly improve VL control. However, the most feasible approach to controlling VL are likely the development of an effective vaccine 44 to protect dogs from being infectious to the sand fly vector, and identifying new methods to prevent infection in canines and humans, such as the use of insecticidal dog collars, 45,46 and insecticidetreated bednets, 47,48 which are promising in reducing canine and human incidence. Future intervention trials should show whether these new tools could be used to develop a sustainable VL prevention and control strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Such information is important as promoting population expansion of genetically determined resistant dogs would significantly improve VL control. However, the most feasible approach to controlling VL are likely the development of an effective vaccine 44 to protect dogs from being infectious to the sand fly vector, and identifying new methods to prevent infection in canines and humans, such as the use of insecticidal dog collars, 45,46 and insecticidetreated bednets, 47,48 which are promising in reducing canine and human incidence. Future intervention trials should show whether these new tools could be used to develop a sustainable VL prevention and control strategy.…”
Section: Discussionmentioning
confidence: 99%
“…An example of other possible ways to improve integration might include the supplementation of nutritional interventions (e.g., vitamin A) to mass distribution programs of fine-mesh impregnated bed nets against VL. 40 Nutrition should be adequately addressed in the public sector as well. Also, it cannot be excluded that vulnerability to infection and consequent impact of anthropometrics (nutritional status) may also differ because of parasite differences in each region.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of detailed information on risk factors (cultural, demographic, epidemiologic, clinical, and geographic), use of longlasting insecticide-treated nets seems a suitable method of prevention. Results from studies in North Sudan showed that insecticide-treated nets provided 27% protection from kala-azar (12). Whether similar protection can be achieved in Southern Sudan's disease-endemic areas requires confi rmation because effectiveness is dependent on human and vector behavior (13).…”
Section: The Reviewmentioning
confidence: 99%